A Multi-agent Artificial Immune Network Algorithm for the Tray Efficiency Estimation of Distillation Unit - 史旭华 钱锋 (Chinese journal of chemical engineering, 2012)
Based on the immune mechanics and multi-agent technology, a multi-agent artificial immune network （Maopt-aiNet） algorithm is introduced. Maopt-aiNet makes use of the agent ability of sensing and acting to overcome premature problem, and combines the global and local search in the searching process. The performance of the proposed method is examined with 6 benchmark problems and compared with other well-known intelligent algorithms. The experiments show that Maopt-aiNet outperforms the other algorithms in these benchmark functions. Furthermore, Maopt-aiNet is applied to determine the Murphree efficiency of distillation column and satisfactory results are obtained.